Viscosity modulation of resin composites versus hand application on internal adaptation of restorations - Andrade, Adrielle Caroline Moreira [UNESP]; Trennepohl, Amanda Acioli [UNESP]; Moecke, Sabrina Elise [UNESP]; Borges, Alessandra Bühler [UNESP]; Torres, Carlos Rocha Gomes [UNESP] (Springer Nature, 2022)
Objective: To compare the effect of the injection of viscosity modulated resin composites versus hand application without modulation, on the internal adaptation of different material to the gingival wall of class II preparations. Materials and methods: Class II cavities were created on mesial and distal surfaces of 60 extracted human molars, resulting on 120 tooth preparations (n = 120). The preparations were restored with four resin composites: VIS-VisCalor (Voco); GRA-GrandioSO (Voco); FIL-Filtek One Bulk Fill (3 M/ESPE); and SON-SonicFill (Kerr). Each composite was applied by two different techniques: by hand (H) or assisted (A). For the hand technique, the material was placed into the preparation using a spatula. For the assisted technique, the resin composite was heated up to 65 °C (for VIS, GRA, and FIL) or sonicated (for SON) and injected into the preparation. After the restorative procedures, the teeth were completely demineralized to allow the restoration removal. The total area of the gingival wall and the area occupied by interfacial defects of adaptation (TDA) were measured by optical microscopy and digital software. The percentage of the area occupied by the defects (%TDA) in relation to the total area was calculated. The data were analyzed by two-way ANOVA and Tukey tests. Results: Significant differences were observed for the application technique (p = 0.0403) and for the materials (p = 0.0184), as well for the interaction between them (p = 0.0452). The mean (standard deviation) of %TDA and results of Tukey test for the interaction were as follows: SON/H — 1.04(0.75)a; VIS/A — 2.01(0.92)a; VIS/H — 3.62(0.99)b; GRA/A — 6.23(3.32)b; FIL/H — 7.45(3.31)bc; GRA/H — 9.21(4.53)c; SON/A — 11.26(4.04)a; FIL/A — 17.89(5.08)d. Conclusion: The injection of heated resin composites improves the adaptation to the walls in relation to the hand technique for VisCalor and GrandioSO but worsens for Filtek One. Sonic vibration increases the number of interfacial defects for SonicFill. Clinical relevance: The physical modulation of the resin composite viscosity can improve or worsen the material adaptation to the walls of class II restoration. It had a positive impact for VisCalor and GrandioSO but a negative for Filtek One and SonicFill.
Keywords: Adaptation; Heat; Resin composite; Sonic; Viscosity; Voids